(untitled) (Journal of Nepal Geological Society, 2019)
Geo-hazards, dynamic Himalayan tectonics, high seismicity, predominant soft rock (argillaceous) formations, steep slopes, rugged (high elevation difference) terrain, when mistreated would trigger-disasters. These natural factors exacerbated by unplanned developments together with impacts of global climate change have further scaled-up disasters in Nepal. Common natural disasters in Nepal impacting the livelihoods of the people below poverty are: earthquakes, floods and landslides. The return period of former is longer (+/- 70 years)but catastrophic, e.g. Gorkha-earthquake, while latter ones are recurrent and chaotic. Substantial efforts have been made on disaster risk reductions (DRR) both by the state and non-state organizations. Contributions from sectoral ministries led by the Ministry of Home Affairs are primarily focused to legal provisions, strategies and policies while the departments are mandated to implement sectoral activities through projects and programs. Post Gorkha-earthquake rescue and relief operations demonstrated an exemplary solidarity among national, bilateral and international organizations. Reconstruction works are rather slow and still being continued. Despite substantial DRR efforts, outcomes are not satisfactory to the desired extent, whether it is earthquake or are floods and landslides across the country as per media and public voices reported. This paper aims to analyse some key questions towards effective and sustainable disaster risk management in Nepal against existing challenges and gaps in the backdrop of Sendai Framework for Disaster Risk Reduction (SFDRR) 2015-2030. A theory of change that would help improve effectiveness and sustainability of disaster risk management (DRM) in Nepal is envisioned and discussed